PERANAN BAGI PENDIDIKAN NASIONAL - Japarlin Marbun (Program Studi Pendidikan Agama Kristen, 2016)
The Church's role in education has to be real, the proportion should be clear. Why? Because the church may not get appreciation in education if the church is not able to provide the benefits. This is a problem that should be taken serious with church. The main solution to the problems of education is the provisition of human resources (HR) that have excellence of visition, professional expertise, farsighted, visionary and highly competitive. Human resources (HR) as this would have a high confidence and skills appropriate bargaining power market. In addition to human resources (HR, other solutions are needed to address the problem of education is the provision of facilities that are useful and appropriate quality demands. With participating from human resources and facilities like that, obviously the church has supported the government to achieve national education goals. Absrak: Peranan gereja dalam pendidikan harus nyata. Proporsi itu harus jelas. Kenapa? Sebab gereja tidak mungkin mendapat pengakuan dalam pendidikan kalau dirinya tidak mampu memberikan manfaat. Ini adalah problema yang harus ditanggapi gereja dengan serius. Solusi utama terhadap masalah-masalah utama pendidikan adalah pengadaan sumber daya manusia (SDM) yang berwawasan keunggulan, berkeahlian professional, berpandangan jauh ke depan (visioner, dan berdaya saing tinggi. SDM seperti ini akan memiliki rasa percaya diri yang tinggi dan keterampilan sesuai daya tawar pasar. Selain SDM, solusi lain yang diperlukan untuk mengatasi masalah pendidikan adalah penyediaan fasilitas yang bermanfaat dan berkualitas sesuai tuntutan kebutuhan. Dengan menyumbangkan SDM dan fasilitas seperti itu, jelas gereja telah mendukung pemerintah mewujudkan tujuan Pendidikan Nasional.